Comparative Life Cycle Assessment of Gasification and Landfilling for Disposal of Municipal Solid Wastes - Angelika Sita Ouedraogo; Robert Scott Frazier; Ajay Kumar (Energies, 2021)
Disposal of municipal solid wastes (MSW) remains a challenge to minimize its impacts on the environment and human health. Landfilling, currently the most common method used for MSW disposal, occupies land space and leads to soil and air emissions. Gasification, an alternative MSW disposal method, can convert waste to energy, but can also lead to soil and air emissions and is a more extensive operation. In this study, life cycle assessments (LCA) of the two disposal methods (landfilling without energy recovery and gasification) were compared to understand impacts on environment and health. The LCA was conducted following the ISO 14040 standards with one ton of MSW as the functional unit. The life cycle inventory was obtained from published journals, technical reports, LandGEM, HELP and GREET database. The impact assessment was done using TRACI 2.1 and categorized into eight groups. The LCA revealed that landfilling is a higher contributor in global warming, acidification, smog formation, eutrophication, ecotoxicity and human health cancer and non-cancer categories. The negative environmental impacts of MSW landfilling can be primarily attributed to the fate of leachate loss and landfill gas, while those of the MSW gasification can be attributed to the disposal of its solid residues.